Arte construtiva brasileira: o uso de materiais pictóricos industriais pelos artistas nas décadas de 1950 e 1960 - Joao Henrique Ribeiro Barbosa (2017)
The aim of this research is to understand the availability of artistic and industrial paint materials in Brazilian constructive art during the 50s and 60s. This work is included in the research Brazilian Concrete Art: The Material of Form. This one results from the project The Material of Form: Industrialism and the Latin American Avant-Garde developed by the Getty Conservation Institute. This dissertation contains three sections. The first one presents the Brazilian artistic context during the 50s and 60s. It will be discussed concepts about constructive art, concrete art and the neoconcrete movement, and what characterize the movements launched by the paulistas of Rupturas Group and cariocas of Frentes Group and Neoconcretism. The second chapter starts with a brief industrial and economical context of Brazil, emphasizing cities like São Paulo, Rio de Janeiro, and Minas Gerais. In order to understand the diversity of terms used in the description of synthetic resins available in the beginning of the XIX century, we will show what the meaning of oil paint, "nitrocellulose, alkyd, vinyl and acrylic paint according to paint manufacturers during the 60s. After that, we will refine on the discussion of department stores responsible for selling and distributing those products. Besides we also will detail national and international paint companies, their brands and product lines. This chapter also proposes a social reflexion about Brazilian's autonomy rush, particularly in the synthetic resins production in the 50s. This situation is fully debated by Iberê Camargo at the Salão Preto e Branco (1954) and Miniatura (1955). The third chapter tries to relate the artistic and materials definitions. We try to emphasize the different characteristics of concrete art in São Paulo and Rio de Janeiro with a view on the option for industrial materials, In this chapter, we will also choose to highlight Ivan Serpas and Mario Silésios choice of materials and their intention.